A comparison between averaged spikes and individual visually-analyzed spikes in rolandic epileptiform discharges - Braga,Nadia I.O. (2002)
PURPOSE:This study compared some morphological features of individual rolandic epileptiform discharges, used to obtain an averaged estimate, with those of the resulting estimate. METHOD: Twenty-four averaged discharges from EEGs of 24 children showing rolandic spikes were compared with 480 individual discharges used in the averaging. The analysis was based on the occurrence of tangential dipole and "double spike" patterns. RESULTS: In 15 averaged discharges the tangential dipole pattern was found. Individual spikes used in the averaging process displayed the same pattern in 35-100% of them; in the remaining 9 averaged discharges, up to 20% of the individual spikes showed the same pattern, although this was not found in the averaged waveforms. "Double spike" pattern was found in 11 of the averaged waveforms and was recognized in 50-100% of its individual discharges, whereas up to 45% of individual spikes showed this pattern without expression in the averaged waveform. CONCLUSION: When visually analyzing an EEG with rolandic spikes, caution should be exercised in characterizing these patterns, since a few discharges showing them may not be expressed in the averaged waveform and the clinical correlations proposed for these patterns may not apply.